Dual‐Mode Self‐Powered Rainfall Sensor Based on Interfacial‐Polarization‐Enhanced and Nanocapacitor‐Embedded FCB@PDMS Composite Film. Issue 6 (9th February 2022) - Mu, Jiliang; Song, Jinsha; Han, Xiaotao; Xian, Shuai; Hou, Xiaojuan; He, Jian; Chou, Xiujian
Abstract: The uneven time‐space distribution of rainfall can easily induce droughts and floods disasters. Meteorological sensor based on battery supply plays an important role to monitor and warn rainfall intensity, however it is limited by the frequent replacement of battery. In this paper, a dual mode self‐powered rainfall sensor (DSR‐Sensor) based on hybrid enhanced triboelectric nanogenerator (TENG) is first proposed. The DSR‐Sensor is fabricated with frictional layer of polydimethylsiloxane (PDMS) and the electrode layer of Cu. These layers are assembled into TENG composed of single electrode mode and contact separation mode. To increase the specific surface, the surface of PDMS film is modified by microimprint process. To accumulate more induced charges, the film is further doped with nanoparticles of fluorinated carbon black based on the effect of nanocapacitor interface polarization. The measured rainfall intensity ranges from 0.1 to 12 mm min −1, which has obvious advantage compared with the ordinary commercial sensor. The sensitivity and linearity are 5.5237 V mm min –1 and 0.9692, respectively. Also, the electrical output performances keep well in multiple tests of continuous 600 s within one month, which shows excellent stability. These results suggest great realistic potential of the self‐powered DSR‐Sensor in the field of meteorological environment monitoring. Abstract : A dual‐mode self‐powered rainfall sensor is reported. To increase the specific surface, the surface modified micro‐pyramid‐arrays PDMS (m‐PDMS) friction layer and micro‐Cu electrode are designed. The m‐PDMS is doped with nanoparticles of FCB to enhance charge storage capacity based on nanocapacitor interface polarization effect. The sensor can monitor rainfall intensity ranged from 0.1 to 12 mm min −1 in real‐time.